Compensating displaced workers - Donald O. Parsons (IZA World of Labor, 2018)
Job displacement poses a serious earnings threat to long-tenured workers through unemployment spells and lower re-employment wages. The prevailing method of insuring job displacement losses involves an uncoordinated combination of unemployment insurance and severance pay. Less developed countries often rely exclusively on public mandating of employer severance pay due to the administrative complexity of unemployment insurance systems. If both options are operational, systematic integration of the two is important, although perhaps not possible if severance pay is voluntarily provided.
Keywords: J65; J41; J33; J08; 330; job displacement; unemployment insurance; wage insurance; severance pay